Palestine in Israeli School Books : Ideology and Propaganda in Education. - Peled-Elhanan, Nurit (I.B. Tauris, 2013)
Each year, Israel's young men and women are drafted into compulsory military service and are required to engage directly in the Israeli-Palestinian conflict. This conflict is by its nature intensely complex and is played out under the full glare of international security. So, how does Israel's education system prepare its young people for this? How is Palestine, and the Palestinians against whom these young Israelis will potentially be required to use force, portrayed in the school system? Nurit Peled-Elhanan argues that the school books used in the educational system are embued with an anti-P.